Three-dimensional phase-field modeling of temperature-dependent thermal shock-induced fracture in ceramic materials - Li, Dingyu (2022)
Current theoretical and experimental methods cannot fully reveal the mechanisms of the rapid and complex thermal shock-induced crack initiation and propagation processes in ceramic materials. Herein, a three-dimensional (3D) coupled thermo-mechanical phase-field model (PFM) is developed for thermal shock-induced fracture with the consideration of the temperature dependence of material properties. Compared with other PFMs, the present model can eliminate the unexpected damage evolution at the initially intact area of materials by introducing a temperature-dependent fracture energy threshold. Both the two-dimensional (2D) and 3D phase-field modeling results of thermal shock-induced fracture show strong agreement with the experimental results. The net-like topologies of thermal shock-induced cracks on the specimen surfaces are captured. Specifically, the crack topologies on the bottom surface (i.e., the first part submerged in water) are significantly different from those on the top surface in 3D cases. These essential findings reveal the mechanism that the tensile part of the strain energy mainly dominates the thermal shock-induced cracking in ceramics.